Contribution of Hsa-Mir-146A and Hsa-Mir-223 Gene Variations in Patients with Multiple Sclerosis Reveals Association of Rs2910164 and Rs1044165 with Risk of Multiple Sclerosis Susceptibility. (June 2021) - Shareef, Salar; Ebrahimi, Seyed Omar; Reiisi, Somayeh
MicroRNAs (miRNAs) are a group of non-coding RNAs that play a role in gene regulation. Due to their possible functional importance, genetic variants within miRNA genes have been recognized as candidate biomarkers. Single-nucleotide polymorphisms (SNPs) in miRNA genes can be related to the risk of different autoimmune diseases. Some of these SNPs are rs2910164 in the miR-146a and rs1044165 in the miR-223. The aim of this study was to investigate the relationship between these polymorphisms and the risk of multiple sclerosis (MS) in an Iranian population. In this case-control study, 261 patients with MS and 250 healthy controls that matched by age and geographical region were enrolled. After sampling and genomic DNA extraction, genotyping was determined by PCR-restriction fragment length polymorphism. Allelic and genotypic associations between the SNPs and MS were evaluated by the data analysis conducted by SPSS V.20. The frequencies of rs2910164 and rs1044165 SNPs were significantly different between the patients with MS and healthy controls. C and T alleles in the variants rs2910164 and rs1044165, respectively, are associated with increased risk of MS. Such association was obtained in codominant, dominant, and overdominant models for both variants (OR ∼3 and OR ∼1.5, respectively). Furthermore, this study determined that the C and T alleles of rs2910164 and rs1044165 are risk factors for MS in the Iranian population.